2019
DOI: 10.1021/acs.est.9b04616
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Interplay Predominated by Beneficial Aspergillus Abates Fungal Pathogen Incidence in Paddy Environment

Abstract: Rice fungal pathogens, responsible for severe rice yield loss and biotoxin contamination, cause increasing concerns on environmental safety and public health. In the paddy environment, we observed that the asymptomatic rice phyllosphere microenvironment was dominated by an indigenous fungus, Aspergillus cvjetkovicii, which positively correlated with alleviated incidence of Magnaporthe oryzae, one of the most aggressive plant pathogens. Through the comparative metabolic profiling for the rice phyllosphere micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Among them, 2(3H)-benzofuranone, 2,4-bis(1,1-dimethylethyl)-phenol, and butyl isobutyl phthalate exhibited high antifungal and antibacterial activities. 2(3H)-benzofuranone produced by the indigenous fungus remarkably inhibited the mycelial growth of M. oryzae (Fan et al, 2019). 2,4-bis(1,1-Dimethylethyl)-phenol effectively inhibited the spore germination of P. cinnamomi and Aspergillus and controlled tomato fungal diseases such as early blight and gray mold (Rangel-Sánchez et al, 2014;Gao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 2(3H)-benzofuranone, 2,4-bis(1,1-dimethylethyl)-phenol, and butyl isobutyl phthalate exhibited high antifungal and antibacterial activities. 2(3H)-benzofuranone produced by the indigenous fungus remarkably inhibited the mycelial growth of M. oryzae (Fan et al, 2019). 2,4-bis(1,1-Dimethylethyl)-phenol effectively inhibited the spore germination of P. cinnamomi and Aspergillus and controlled tomato fungal diseases such as early blight and gray mold (Rangel-Sánchez et al, 2014;Gao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As reported, after the MoPER1 gene was knocked out or its expression was inhibited, the fungi was defective in growth, pathogenicity, and cell wall integrity, which indicated that MoPer1 plays an important role in the growth, development and pathogenicity of M. oryzae (Chen et al, 2018;Fan et al, 2019). To investigate MoPer1 protein's effect mechanism in M. oryzae, we applied the TMT quantitative and qualitative analysis technique to examine the DEPs between the DMoper1 mutant and Guy11.…”
Section: Discussionmentioning
confidence: 98%
“…The bacteria were isolated by the plate dilution method according to Fan et al [ 33 ] with minor modifications. Ground and homogenized tomato leaves with MSe2.0 treatment (of Experiment I ) were diluted to 10 −1 –10 −5 concentration gradient, 100 μL was coated on Beef Extract Peptone Agar Medium plate, incubated at 30 °C for 24 h, and the colonies with different morphology and color were purified then stored at 4 °C.…”
Section: Methodsmentioning
confidence: 99%